Molecular investigation of Mycoplasma haemofelis in stray cats in Kota Bharu, Kelantan - Aklilu, E; Shaharulnizim, N.; Francis, J.J.; Anurrdin, S.H. (Malaysian Society of Parasitology and Tropical Medicine, 2016)
Mycoplasma haemofelis (M. haemofelis) is a gram-negative, epicellular bacteria that infects feline red cells (RBC). The pathogen appears as small blue cocci, rings, or rods on the edges or across the surface of RBCs and often causes haemolytic anemia. However, the epizootiology of M. haemofelis is still poorly understood. So far, there are only a few studies that have been carried out to determine the prevalence of M. haemofelis. Most of the studies were conducted in Europe and other continents and the epidemiology of M. haemofelis in Malaysia, particularly in stray cats have not been reported. In this study, 60 blood samples were collected from stray cats in Kota Bharu and were examined by using thin blood smear and polymerase chain reaction (PCR) methods. This study showed that seven out of the 60 blood samples were positive for M. haemofelis by using PCR. Thus the prevalence rate of M. haemofelis in stray cats in Kota Bharu from this study was 11.7%. However, more studies with larger sample size and diverse sample distribution should be conducted to better understand the occurrence of this pathogen in both housed and stray cats. Moreover, the genetic variability of M. haemofelis infecting domestic and wild animals need to be conducted to verify the relationship among geographic distribution, genetic diversity and the potential threats to animal and human health.